DEVELOPING A WORKBOOK OF BASIC LISTENING COURSE FOR THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT IAIN ANTASARI BANJARMASIN - Hidayah Nor; Nur Alfa Rahmah (Vision: Journal for Language and Foreign Language Learning, 2015)
Work book is one of the principal necessities in the process of teaching and learning second language. A comprehensive work- book will work as step-by-step guidance both for the teacher and students; teacher will know what to do to transfer the knowledge effectively within very limited time constraint; and students will be provided clear clue to comprehend required materials and acquire the necessary skills. Without work book, teacher will have to think and work harder in every meeting to measure their students’ needs and adapt the materials to their comprehension capacity. Third semester students of English Teaching Department of IAIN Antasari Banjarmasin can be classifi ed as beginning learners of English. For most students who live in a non-speaking English country such as Indonesia, listening skill is diffi cult to comprehend. Listening skills is seen not only as something valuable for its own sake but as something that supports the growth of other as- pects of language use, such as speaking and reading. The assump- tions of teaching listening as comprehension are: listening serves the goal of extracting meaning from messages, the learners have to be taught how to use both bottom up and top down processes in arriving at an understanding of messages, and the language of ut- terances used by speakers are temporary carriers of meaning. Once meaning has been identifi ed there is no further need to attend to the form of messages. Students have problems to catch the actual sounds of the for- eign language; understand every word which make them feel wor- ried and stressed; understand fast, natural native-sounding speech; keep up with all the information they get and they cannot predict. To overcome these problems teachers can help students by teach them how to improve their listening through some skills and teach the students by using media. Dealing with the purpose of this research in developing work- book for English listening class, the suitable design for this research is research and development (RD).